Technological Change and the Boundaries of the Firm - Lewis, Tracy R.; David E. M. Sappington (American Economic Review, 1991)
We examine a firm's decision either to produce an essential input itself or to hire a subcontractor to produce the input. We focus on how this decision is affected by technological change in the industry. In general, cost-reducing technological change leads the firm to produce the input itself more often. The firm's calculus is shown to depend on whether the subcontractor's skills are idiosyncratic or transferable. In the latter case, technological progress can even be detrimental to the firm and to society as a whole.